Pengaruh atraksi, lokasi, dan harga terhadap keputusan berkunjung wisatawan di Hutan Pinus Pengger Bantul Daerah Istimewa Yogyakarta - Endang Widayati; Yoga Pradana Widiastuti (STIE Pariwisata API Yogyakarta, 2022)
This study aims to analyze the effect of attractions, location and price on the decision to visit the Hutan Pinus Pengger (Pengger Pine Forest), Bantul DIY. The method used is quantitative. The research process is deductive in nature to prove the hypothesis by using inferential statistics. The sampling technique used is nonprobability with purposive sampling. The number of samples is 100 respondents. the validity of the instrument was tested by validity and reliability test. To obtain accurate quantitative data, a Likert scale is used. The data used is primary data, which is used to determine respondents' perceptions of the variables of attraction, location and price as well as visiting decisions which are described in 29 statement items. Secondary data is also used to determine the number of tourists. The results showed that the attractions and location variables had a positive and significant effect on the decision of tourists to visit the Pengger Pine Forest. Meanwhile, the price variable has no significant effect on the decision of tourists to visit the Pengger Pine Forest